Political economy of statebuilding power after peace - Berdal, Mats R. 1965-; Zaum, Dominik (Routledge studies in intervention and statebuilding, 2013)
This volume examines and evaluates the impact of international statebuilding interventions on the political economy of conflict-affected countries over the past 20 years. It focuses on countries that are emerging, or have recently emerged, from periods of war and protracted conflict. This book will be of interest to students of statebuilding, humanitarian intervention, post-conflict reconstruction, political economy, international organisations and IR/Security Studies in general.